Aplikasi Penggalangan Dana Sosial Berbasis Android & SQLite - Syahrin, Muhammad Alfi; Mei Prianto, Ega (Himpunan Dosen Gemilang Indonesia (HDGI), 2023)
Every year the development of information and communication technology is getting more advanced so that it has an impact on the ease of humans in completing every job including data collection activities. Case in point in the social fundraising data collection system, data collection activities still use a manual system which still uses books as a data storage medium. This is considered inefficient in terms of time, cost, data security and the energy spent by the owner of the rental house in data collection activities. As well as causing difficulties in obtaining personal information related to available Social Fundraising. These problems provide a clear picture of why an adequate and computerized Social Fundraising data collection system is needed. This system research uses R&D research methods. The results of the application research can run well based on testing the Create, Read, Update, Delete (CRUD) operations with the SQLite database implementation